Autophagy inhibition facilitates wound closure partially dependent on the YAP/IL‐33 signaling in a mouse model of skin wound healing. Issue 10 (21st September 2021) - Gao, Yuan; Luo, Chengliang; Rui, Tongyu; Fan, Yanyan; Yao, Yi; Shen, Hengji; Gao, Cheng; Wang, Tao; Wang, Haochen; Chen, Xueshi; Zhang, Jiaxin; Li, Dongya; et al.
Abstract: Autophagy is a self‐phagocytic and highly evolutionarily conserved intracellular lysosomal catabolic system, which plays a vital role in a variety of trauma models, including skin wound healing (SWH). However, the roles and potential mechanisms of autophagy in SWH are still controversial. We firstly investigated the role of autophagy in SWH‐induced wound closure rate, inflammatory response, and histopathology, utilizing an inhibitor of autophagy 3‐methyladenine (3‐MA) and its agonist rapamycin (RAP). As expected, we found 3‐MA treatment remarkably increased the wound closure rate, combated inflammation response, and mitigated histopathological changes, while RAP delivery aggravated SWH‐induced pathological damage. To further exploit the underlying mechanism of autophagy regulating inflammation, the specific inhibitors of yes‐associated protein (YAP), Verteporfin, and Anti‐IL‐33 were applied. Herein, treating with 3‐MA markedly suppressed the expression of tumor necrosis factor‐α (TNF‐α), IL‐1β, and IL‐6, promoted that of IL‐10, IL‐33, and ST2, while RAP administration reverted SWH‐induced the up‐regulation of these inflammatory cytokines mentioned above. Importantly, Verteporfin administration not only down‐regulated the expression levels of YAP, TNF‐α, and IL‐6 but also up‐regulated that of IL‐33 and IL‐10. Unexpectedly, 3‐MA or RAP retreatment did not have any impact on the changes in IL‐33 among these inflammatory indicators. Furthermore, elevated expression of IL‐33 promoted wound closure and alleviated the pathological damage, whereas, its antagonist Anti‐IL‐33 treatment overtly reversed the above‐mentioned effects of IL‐33. Moreover, 3‐MA in combination with anti‐IL‐33 treatment reversed the role of 3‐MA alone in mitigated pathological changes, but they failed to revert the effect of anti‐IL‐33 alone on worsening pathological damage. In sum, emerging data support the novel contribution of the YAP/IL‐33 pathway in autophagy inhibition against SWH‐induced pathological damage, and highlight that the autophagy/YAP/IL‐33 signal axis is expected to become a new therapeutic target for SWH.